Influence of microstructure topology on the mechanical properties of powder compacted materials. (15th May 2021) - Lai, Chang Quan; Seetoh, Ian
Highlights: General structure – property relationships were derived for porous materials of 3 main topologies up to relative densities of ~ 0.9. Compared theoretical and simulation trends against literature experimental data obtained from powder compaction studies. Results suggests that foams are probably stretch-/ compression- dominated for relative densities above 0.4, instead of being bending-dominated for all relative densities, which is the current understanding. Results also indicate that joint ( i.e. particulate) rotation in the microstructure is probably the leading cause of low moduli observed in powder compacted materials, while their weak strength stems from the small area of narrow neck-like interparticle connections. Analysis suggests that higher coordination number of the particles can reduce particulate rotations, and thus, improve the stiffness of powder compacted materials. Abstract: Powder compaction is an important technique for fabricating engineering materials as it offers good resolution and is compatible with complex stoichiometry and geometries. It forms the basis of important manufacturing processes such as powder bed 3D printing, powder metallurgy and metal injection moulding. However, a major disadvantage is that the presence of porosity in the resultant material can lead to a drastic deterioration of its mechanical properties. To improve the stiffness and strength of these powder compacts, it is imperative to pinpoint the main cause of these weakening effects. Here, we attempt to do so by examining the mechanics of different topologies that the microstructures of powder compacted materials can adopt. General structure – property relationships were first derived for (i) compression/ stretch – dominated (CD) (ii) compression, shear and bending (CSB) and (iii) compression, shear and joint rotation (CSR) topologies, for the range of relative densities between 0 and ~ 0.9. Using the Face-Centered Cubic (FCC), Body-Centered Cubic (BCC) and 3D Anti-Tetrachiral (3ATC) geometries to represent the CD, CSB and CSR topologies respectively, the analytical and simulated relative stiffness vs. relative density and relative strength vs. relative density trends were compared against experimental data in the literature. It was found that the mechanical properties of powdered materials typically fall within an exclusive range of values exhibited by the 3ATC lattice, which is much lower than that expected of FCC and BCC lattices. A closer examination of the analytical equations indicated that the low modulus of 3ATC lattices and powder compacted materials is caused by joint ( i.e. particulate) rotation, while their weak strength is the result of thin beams, which manifest as narrow neck-like interparticle connections in powder compacted materials. These results are supported by previous studies, which showed that powder compacted materials have eccentric microstructures similar to 3ATC unit cells and the compression of granular material usually results in extensive particulate rotations. Higher coordination number of the particles is expected to reduce these rotations, thus illuminating the strategy for improving the modulus of powder compacted materials. The material strength, on the other hand, has already been shown to improve with a thickening of the neck regions, which can be achieved through higher sintering temperature, compressive pressure and/ or longer compaction time. Graphical abstract: Image, graphical abstract